A ase of bilateral mammary cancer in a patient submmited to estrogen therapy for prostatic carcinoma - Aizen, Bernardo; Cardozo, Tabaré; Esperón, Ruben (Cirugía del Uruguay, 1983)
... A case of bilateral mammary cancer in a patient submmited to estrogen therapy for evaded (grade . IV) prostatic carcinoma is presented. The ethiologic relationship between the hormonal treatment and the prostatic cancer is discussed. Criteria to settle differences between metastatic mammary tumors and primary cancer related to estrogen therapy are recommended.